2006
DOI: 10.1080/00036840500427171
|View full text |Cite
|
Sign up to set email alerts
|

Relative prices and inflation: new evidence from different inflationary contexts

Abstract: This paper analyzes the relationship between inflation and relative price variability, in the direction of the latter, in two countries with very different inflationary experiences: Argentina and Spain. To address this objective, using disaggregated price indexes (the Wholesale Price Index for Argentina and the Consumer Price Index for Spain), we delimitate different inflationary regimes and compute a set of regressions for each country. Our results suggest evidence in favour of the non-neutrality of inflation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Following work by Mankiw (1994, 1995), more recent studies have also found a relationship between inflation and the skewness of relative price changes (e.g. Debelle and Lamont, 1997;Aucremanne et al, 2002;Caraballo et al, 2006). Although the relative size of the variance and skewness effects is controversial (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…Following work by Mankiw (1994, 1995), more recent studies have also found a relationship between inflation and the skewness of relative price changes (e.g. Debelle and Lamont, 1997;Aucremanne et al, 2002;Caraballo et al, 2006). Although the relative size of the variance and skewness effects is controversial (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, this result is robust to different time periods as Table 5 shows. 9 Moreover, inflation expectations and uncertainty can be the underlying causes behind this kind of relation (see, for example, Caraballo et al 2006, Caraballo and Dabús 2008, Caglayan et al 2008, Becker and Nautz 2009band Choi 2010. This issue is studied in the next section.…”
Section: [Table 5 Here]mentioning
confidence: 99%
“…8 We compute the annual inflation for each month, with respect to the 6 Only a few previous studies covered such high rates of inflation along with considerably lower values. In this regard, Choi et al (2011) constitutes the main exception together with Caraballo et al (2006) and Caglayan and Filiztekin (2003).…”
Section: Data and Estimationmentioning
confidence: 99%
“…Jaramillo (1999) showed that in the U.S., the impact of inflation on RPV, while always positive, is stronger when it is below zero. Similarly, Caraballo et al (2006) report that for Spain and Argentina, the positive effect is stronger when inflation is high and exploded during the hyperinflationary period in Argentina. Using data from Turkey, Caglayan and Filiztekin (2003) also showed that the association is significantly different during low and high inflation periods.…”
Section: Introductionmentioning
confidence: 99%